Dynamic System Modeling Analysis of CPO-FAME-Biodiesel Distribution for B40 Quota Fulfillment in Java Island 2025 - Shaleha, Rahma Luthfia; Oetomo, Dedy Setyo; Ramdhani, Rizky Fajar (Journal of Information System, Technology and Engineering, 2025)
This research aims to analyze the distribution cost structure and transportation requirements for CPO-FAME-Biodiesel to meet B40 quota implementation in Java Island using a dynamic system approach. This study uses dynamic system simulation with Vensim software to model CPO-FAME-Biodiesel distribution from Sumatra and Kalimantan to Java Island, utilizing data from Ministry of Energy and Mineral Resources and GAPKI with 2025 projections. The simulation reveals that meeting the B40 quota in Java Island requires substantial infrastructure investment with total transportation costs exceeding IDR 1.3 trillion, highlighting the massive scale and logistical complexity of national biodiesel implementation. Analysis identifies fleet tariff, shipping frequency, fleet capacity, raw material prices, and conversion ratios as the primary cost drivers affecting distribution efficiency. Cost optimization can be achieved through strategic shipping frequency management, capacity optimization, efficient fleet fuel management, and implementation of centralized production systems with hub-and-spoke distribution networks. This research contributes essential strategic insights for policymakers in developing cost-effective transportation frameworks and infrastructure planning for Indonesia's national biodiesel policy implementation.